ANALISIS IMPLEMENTASI STANDAR KOMPETENSI KEMANDIRIAN PESERTA DIDIK TINGKAT SATUAN PENDIDIKAN DASAR PADA ASPEK PERKEMBANGAN EMOSI - Intan Sari; Sabarrudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Guidance and counseling in elementary schools should not be regarded merely as a conceptual discourse; rather, it must function as a strategic educational service that supports students in achieving their developmental tasks holistically. These developmental domains include social, spiritual, moral, intellectual, and emotional aspects. As learners who are in the process of developing these competencies, students require guidance to attain the standards of student independence competencies (Standar Kompetensi Kemandirian Peserta Didik/SKKPD). The SKKPD encompasses eleven developmental aspects, one of which is emotional maturity. Recent cases of bullying reported in both online and offline media highlight the urgency of fostering emotional maturity among school-aged children. These incidents have drawn public attention due to the emergence of aggressive behaviors among students, often triggered by their inability to regulate emotions in a healthy manner. This article aims to analyze the internalization process of emotional maturity, which can be conceptualized through three stages. The first stage is recognition, during which individuals learn strategies to avoid interpersonal conflict. The second stage is accommodation, defined as the ability to tolerate various ways in which others—and oneself—express emotions. The third stage is action, which involves expressing emotions freely and openly while avoiding behaviors that may provoke conflict. This study employs a literature review methodology. Such a method constitutes an essential component and often serves as the primary foundation in qualitative research as well as in purely library-based studies. The findings indicate that the implementation of the SKKPD, particularly in the domain of emotional development, is crucial for assisting school counselors in facilitating elementary students’ abilities to recognize and manage their emotions effectively.